Tensile properties of untreated bambusa vulgaris, gigantoch- loa levis gigantochloa scortechinii, gigantochloa wrayi, and schizostachyum zollingeri bamboo fibers - Mat Jais, Fatin Nadiah; Roslan, Mohd Nazrul; Nasir, Siti Hana; Baharuddin, Norhazaedawati; Uyup, Mohd Khairun Anwar (WARSE, 2020)
In the last couple decades, bamboo is getting interest due to the usefulness in textile application beside the most sustainable plant in earth. Textile fiber requires physically long, featherweight, and fine in diameter. Bamboo fibers impose high cellulose and lignin content. In a single fiber form, bamboo has very short physical length which lesser than 4 mm. This natural characteristic could affect the mechanical properties in fiber bundle or long fiber formation for textile processing. Besides, the extraction of long and fine bamboo fibers is significantly challenging over different species of them. Therefore, the tensile behavior of the untreated bamboo fibers over variety species shall be understanding in-depth. This study is about identifying tensile properties of bamboo fiber bundle of five commercialized bamboo species in Malaysia. Three regions of fiber bundles locations were extracted mechanically and tested. The long bamboo fiber tenacity and fineness were examined besides tensile strength and strain to failure value. Among those species, G. levis species demonstrated the highest tensile strength around 98MPa with strain to failure at 4.51%. G. wrayi (BT) recorded the coarsest fiber at 231 tex while the highest tenacity was obtained by B. vulgaris (MYK) at 10.88 cN/tex.